Concise Review: Is Cardiac Cell Therapy Dead? Embarrassing Trial Outcomes and New Directions for the Future. (22nd February 2018) - Tang, Jun‐Nan; Cores, Jhon; Huang, Ke; Cui, Xiao‐Lin; Luo, Lan; Zhang, Jin‐Ying; Li, Tao‐Sheng; Qian, Li; Cheng, Ke
Abstract: Stem cell therapy is a promising strategy for tissue regeneration. The therapeutic benefits of cell therapy are mediated by both direct and indirect mechanisms. However, the application of stem cell therapy in the clinic is hampered by several limitations. This concise review provides a brief introduction into stem cell therapies for ischemic heart disease. It summarizes cell‐based and cell‐free paradigms, their limitations, and the benefits of using them to target disease.Stem Cells Translational Medicine 2018;7:354–359 Abstract : Summary outlining barriers and solutions to cell therapy. Stem cell therapy is a promising strategy for cardiac tissue regeneration. However, the application of stem cell therapy in the clinic is hampered by several limitations. Despite these hurdles, a number of alternative and ever‐evolving solutions involving cell based and cell free paradigms, offer promising therapy options for patients with cardiac disease.